PENGATURAN PERKAWINAN PADA GELAHANG DALAM AWIG-AWIG DESA PAKRAMAN - I Ketut Sudantra; Ni Nyoman Sukerti; A.A. Istri Ari Atu Dewi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
This article was written based by result of normative legal research about the regulation of padagelahang marriage on customary law that created by customary law society of desa pakraman inBali. That research was aimed to identify legal norms in awig-awig desa pakraman that regulateabout pada gelahang marriage.From that research’s result, it was known that aspect of matrimonial law has been regulated inawig-awig, whic is on certain chapter that regulate family law. That chapter titled Sukerta TataPawongan, that regulate the legal aspects about marriage, divorce, lineage, and inheritance.Although, the research result aslo shown that on nine awig-awig desa pakraman researched, onlyone that regulate about pada gelahang marriage, which is Awig-Wig Desa Pakraman Gadungan(Tabanan). The regulation is rather ambigious, only regulate about recognition of pada gelahangmarriage existance, without any further regulation about requirements, procedure or it’s legalconsequences.